Dominasi Internet di Ruang Publik: Studi Terhadap Penyebaran Wacana Gerakan Bela Islam 212 di Indonesia - Hasse Jubba; Tawakkal Baharuddin; Mustaqim Pabbajah; Zuly Qodir (Institut Agama Islam Negeri Kendari, 2020)
The emergence of the term new media is very closely related to the presence of the internet in human life. Even though in its development, new media is not only limited to the Internet, but the Internet is a tool or media that is used in the era of new media, such as in the events of Bela Islam 212 in Indonesia. The Islamic defense action is known as the Gerakan 212 in coverage in many secular mainstream media and community media among diverse Muslims. The Gerakan Bela Islam 212 was later appreciated as a peaceful act. That is because the action was demonstrated through such a large mass mobilization. This study aims to analyze and study how the dominance of the Internet in public spaces over the spread of discourse on the 212 Islamic movements in Indonesia. The results of this study found that the Internet and social media are new media, with its users able to easily participate, share, and create new spaces in distributing news and discourse on Gerakan Bela Islam 212. Stable Internet penetration and also the use of media networks online is a form of social control tool in a democratic system. Social media is considered capable of mobilizing the masses of the Gerakan Bela Islam 212 in Indonesia to be actively involved and present at the Jakarta Monas. This proves that the Internet dominates public spaces related to the issue of reporting and discourse of Islamic action by the use of social media networks.